Below-the-Knee Amputation by Extern. - Jeeravipoolvarn, Polasak; Mahaizavariya, Banchong; Chaikitpinyo, Sakda; Kowsuwon, Weerachai (Srinagarind Medical Journal, 2013)
This is a prospective study of sixty long posterior flap below-the-knee amputations done by the KhonKaen University externs under closed Supervision of qualified orthopedists. Post-operatively red rubber bulb drainage was used instead of the hemovac.The patients were all leprotic and held in custody by Nonsomboon Leprosarium. Twenty-nine cases were affected by malignant change of the long standing trophic ulcer, while 29 had chronic ulceration and osteomyelittis of the tarsal bones with useless deforned feet. One was due to painful Boyd’s stump and the other form persistent infection after transmetatarsal amputation. Eighteen cases of stitch abscess and two cases of hematoma collection were detceted but no any wound disruption were seen in our series.